Levantamento das subfamílias de Braconidae (Hymenoptera, Ichneumonoidea) em área de diferentes estágios de conservação, no Vale do Paraíba, Estado de São Paulo, Brasil - Barbieri Junior, Celso Alfredo (Universidade Federal de São Carlos, 2011)
Was conducted a survey of the subfamilies of Braconidae (Hymenoptera) on tree different ecosystems of Vale do Paraíba region, São Paulo state, Brazil: a degraded pasture, a secondary forest and an area in the recovery process, using native tree seedlings, during the period of September, 2007 to August of 2009. The objective was to verify the use of these animals as a tool to check the local conservation by examining the Shannon´s diversity index. Ten subfamilies were identified and Microgastrinae was predominant in number of individuals. The diversities index calculated vary between the sampled areas, thus showing a correlation with vegetation cover with the number of individuals collected and number of subfamilies found. The data analysis showed changes in the community of Braconidae, in the recovery area between the first and second year of study, showing that the community of these animals is highly sensitive and of rapid response to environmental changes, allowing concluding that animals are indicators of environmental quality.
Keywords: Ecologia; Recuperação de áreas degradadas; Diversidade biológica; Indicadores ambientais; Braconidae; Degraded areas; Diversity index; Indicator species; CIENCIAS BIOLOGICAS::ECOLOGIA